Effect of the Monothiol Glutaredoxin GrxD on 2,4-Diacetylphloroglucinol Biosynthesis and Biocontrol Activity of Pseudomonas fluorescens 2P24 - Dong, Qiuling; Yan, Qing; Zhang, Bo; Zhang, Li-qun; Wu, Xiaogang (Frontiers in Microbiology, 2022)
Pseudomonas fluorescens 2P24 is a plant root-associated bacterium that suppresses several soilborne plant diseases due to its production of the antibiotic 2,4-diacetylphloroglucinol (2,4-DAPG). The biosynthesis of 2,4-DAPG is controlled by many regulatory elements, including the global regulator of the Gac/Rsm regulon and the pathway-specific repressor PhlF. In this work, a novel genetic element grxD, which encodes the monothiol glutaredoxin GrxD, was identified and characterized in the production of 2,4-DAPG in P. fluorescens 2P24. Our data showed that the mutation of grxD remarkable decreased 2,4-DAPG production. GrxD lost its ability to alter the production of 2,4-DAPG when the active-site CGFS motif of GrxD was mutated by site-directed mutagenesis. Further studies showed that the RsmA and RsmE proteins were essential for the GrxD-mediated regulation of 2,4-DAPG and exoprotease production. In addition, our data revealed that the deletion of grxD increased the expression of phlF, which negatively regulated the production of 2,4-DAPG. In addition, the grxD mutant was severely impaired in the biocontrol effect against the bacterial wilt of tomato. Overall, our results indicated that the monothiol glutaredoxin GrxD is involved in the production of 2,4-DAPG of P. fluorescens by influencing the Gac/Rsm global signaling pathway and transcriptional regulator PhlF, and is essential for the biocontrol properties.